Deviation from Industry Norms, Financial Restatements and Audit Opinion - Ebrahim Baramzadeh; Seyed Ali Vaez; Ghasem Rekabdar (Iranian Journal of Accounting, Auditing & Finance)
While prior research examines the internal and external factors that influence financial statement restatement and external auditor’s opinion, there is limited research on the impact of deviation from industry norms (DIN) on financial restatements and audit opinion. This study attempts to fill this gap by examining whether and how DIN affects financial restatements and audit opinion. Industry-level risk factors calculate DIN, including annual stock returns, daily return variations, financial distress and leverage. Using a sample of Iranian listed firms (194 firms) between 2014 and 2021, this study documents a significant and positive relationship between DIN with financial restatements and audit opinion, suggesting that firms with higher DIN have higher restatements and are more likely to receive a modified opinion. This paper offers the first empirical research about the consequences of DIN on the restatements and audit opinion at the international level, going beyond the role of firm‐, auditor‐, and governance‐specific characteristics.